Development of STEAM-Based Learning Tools Based on the Sasak Heritage Project - Nurwahidah Nurwahidah; Iva Nurmawanti; Setiani Novitasari; Anindita Suliya Hangesti Mandra Kusuma (Jurnal Penelitian Pendidikan IPA, 2022)
This research is a research and development (R&D) study using the 4-D model. The research aims to produce a valid STEAM learning tool based on the Sasak Heritage Project. The data sources consisted of six expert validators who used validity instruments with four indicators (structure, organization of material, language, and appearance). The research data were analyzed using a quantitative descriptive method. Test the validity of the learning tool using Aiken's V analysis. The results of the validity test show that the STEAM learning tool based on the Sasak Heritage Project is valid, with a minimum validity coefficient of 0.78 for each indicator.